Uric acid detection by means of SERS spectroscopy on dried Ag colloidal drops. (14th January 2016) - Pucetaite, M.; Velicka, M.; Pilipavicius, J.; Beganskiene, A.; Ceponkus, J.; Sablinskas, V.
Abstract : Uric acid concentration in human bodily fluids is an important marker for disorders such as gout, pre‐eclamsia or cardiovascular disease. However, currently used methods for its detection either lack sensitivity or require sophisticated, bulky and expensive equipment. In this work, we show that by using surface‐enhanced Raman scattering spectroscopy (SERS) on dried Ag colloidal drops and with 1064 nm excitation, concentrations of uric acid in aqueous solutions down to 10 −6 M can be detected. Such sensitivity is sufficient for medical applications as concentration of uric acid in various bodily fluids are in the range of 10 −3 –10 −4 M. Drying of the colloidal drops is known to result in the formation of 'coffee‐ring' structures that allow obtaining high enhancements but poor reproducibility. Here, the formation of the structures was avoided by choosing aluminum oxide as a base substrate and by controlling environment conditions. Despite the fact that variations of signal enhancement from sample to sample prevent quantitative analysis from being performed, the results of this work imply that strict control of sample preparation conditions could lead to obtaining reproducible SERS enhancements. Results of density functional theory calculations of uric acid tautomer – five‐atom silver cluster complexes performed for the first time show that the differences between Raman and SERS spectra of uric acid can be mainly explained by tautomerization of the molecule and its bonding to the silver surface. Assignment of spectral bands is important for correct SERS signal interpretation and detection of uric acid in biological fluids in the future studies. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The possibility of detecting low concentrations of uric acid by means of SERS spectroscopy on dried Ag colloidal drops is presented. Differences between SERS and Raman spectra of uric acid are explained by performing density functional theory calculations of uric acid tautomer – five‐atom silver cluster complexes for the first time.